SEMIOTIKA FILM LASKAR PELANGI - Dwi Haryanto (Pascasarjana Institut Seni Indonesia Surakarta, 2011)
Â This article is results of research about of the text of film Laskar Pelangi by Riri Riza. â€œ Issues of concern to this research are: (1) how the shape of the film Laskar Pelangi; (2) how the flow of dramatic film Laskar Pelangi; (3) How does the meaning of the messages contained in the film Laskar Pelangi by Riri Rieza? The purpose of this study is to describe the shape and dramatic plot and interpret the messages contained in the film Laskar Pelangi. Concrete steps to address the problem of research is to describe the shape, dramatic plot and analyze the message conveyed by the scenes at the Rainbow Warriors. In the revealed message conveyed in a movie, it takes an appropriate research methodology to reveal the meaning of the visible and hidden meanings behind the symbols that exist in the film. So the researchers used a qualitative research methodology is interpretive and semiotic approach. This study uses Roland Barthesâ€™s semiotic approach by approaching with five code of the object under study in this movie. Five of them code hermenuitik code, code proaretik, cultural code, code semik and symbolic codes. Semiotic approach is not only researching on the marker and the marker, but also the relationships that bind them as a whole. The results of this study include: movie Laskar Pelangi formed by the elements of narrative and cinematic elements, dramatic plot consisted movie opening phase, middle and closing stages. Film Laskar Pelangi through scenes-scenes convey the message content includes moral messages, the message of leadership, religious messages and social messages. The series of events in a story the film is just a stimulant, it is more important is the messages contained useful to guide the human form of mind and good manners, so that it becomes an adult human being the noble and virtuous character.Keywords: movie Laskar Pelangi, text analysis, the message of education